(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The development of pedagogical abilities and pedagogical skills of students of higher education institutions in the field of preschool education in an integrative direction, positive reaction to them based on advanced teaching methods and a modern approach, teachers in interactive educational processes is recognized as a clear example of effectiveness built on mutual cooperation.